Methodology of Project Management Assessment and the Financial Effects of Its Practices - حسن, بسام; عمران, جمال; ميا, رنا (Latakia University Journal -Engineering Sciences Series, 2019)
A lot of construction projects fail to complete their processes according plans, leading to financial and technical problems. The paper tries to study the extent to which the application of best management practices will have a quantitative measurable effect on project success. We have developed a model (trio assessment methodology) to assess project management maturity for a sample of 18 Syrian projects in Lattakia and Damascus. Results varied with the max was 3 of 5 and a minimum was 1.1. We then applied regression analysis to find the correlation between project management maturity and project performance, represented by cost and duration deviation coefficient. The diagrams showed that there was a strong relation between them. The research introduces a practical tool that project mangers can use to identify the organization ability in order to improve project management and the benefits.